TINDAK TUTUR TOKOH DENGAN GANGGUAN IDENTITAS DISASOSIATIF DALAM NOVEL PERAWAN PALSU KARYA MIEN HIESEL (Universitas Negeri Semarang, 2023)
This study aims to describe the types of speech acts in each character's personality with dissociative identity disorder in Mien Hiesel's novel Perawan Palsu. The dissociative identity disorder of the main character in this novel appears with symptoms of the emergence of three different personality figures in a main character. The research method used is a qualitative descriptive method by implementing a literature review. Collecting data in this study using a read-note technique, then analyzed with the stages of data identification, presentation of conclusion drawing data. The results obtained in this study are that the character with Muya's personality uses four types of speech acts, namely assertive, expressive, directive and commissive. While the character with Laksmi's personality uses five types of speech acts, namely assertive, expressive, directive, commissive and declaration. And the character with Miya's personality uses three types of speech acts, namely assertive, directive and commissive. The character with Muya's personality is very dominant using directive speech acts, the character with Laksmi's personality is dominant using expressive and commissive speech acts, while the character with Miya's personality is dominant using assertive speech acts. The dominant types of speech acts in each of these personalities are in line with the character of their personalities.